The myeloid switch: immune drivers in atopic dermatitis — roles in pathogenesis and emerging therapeutic targeting - Kupschke, Erik; Schenk, Mirjam (Frontiers in Immunology, 2025)
Atopic dermatitis (AD) is one of the most common chronic inflammatory skin diseases worldwide, significantly impairing patients’ quality of life. It is characterized by recurrent eczematous lesions, intense pruritus, and disruption of the epidermal barrier. The pathogenesis of AD is multifactorial and involves complex interactions between genetic predisposition, environmental triggers, skin barrier defects, microbial dysbiosis, and immune dysregulation. While much of the research in recent decades has focused on the type 2 helper T cell (Th2)-driven adaptive immune responses that dominate the acute phase of the disease, the role of innate immunity—particularly that of myeloid cells—has emerged as a crucial and underrated component in disease pathogenesis and progression. This review highlights recent findings on the role of myeloid cells in the initiation, maintenance, and amplification of inflammation in AD. Myeloid cells respond to a wide range of environmental and tissue-derived triggers, including cytokines, alarmins, and microbial products. Upon activation, they contribute to the inflammatory milieu by producing chemokines and cytokines, presenting antigens, and recruiting other immune cells to the skin. Importantly, myeloid cells not only shape the local immune landscape but also engage in crosstalk with keratinocytes and adaptive immune cells, thereby reinforcing chronic inflammation. In addition, the review outlines emerging therapeutic strategies aimed at modulating myeloid cell function or selectively targeting pro-inflammatory subsets. These approaches offer promising avenues that complement existing Th2-centered therapies, addressing disease mechanisms beyond the adaptive immune response. A deeper understanding of the diverse and dynamic roles of myeloid cells in AD may thus support the development of more comprehensive and personalized treatment strategies for long-term disease control.